Optimal refund mechanism - Qianjun Lyu (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper studies the optimal refund mechanism when an uninformed buyer can privately acquire information about his valuation over time. In principle, a refund mechanism can specify the odds that the seller requires the product returned while issuing a (partial) refund, which we call stochastic return. It guarantees the seller a strictly positive minimum revenue and facilitates intermediate buyer learning. In the benchmark model, stochastic return is sub-optimal. The optimal refund mechanism takes simple forms: the seller either deters learning via a well-designed nonrefundable price or encourages full learning and escalates price discrimination via free return. This result is robust to both good news and bad news framework.
Keywords: D82; D86; L15; 330; buyer learning; refund contract; information design; implementable mechanism